XR Accessibility Initiatives in Academic Libraries. Issue 1 (13th October 2021) - Lischer‐Katz, Zack; Clark, Jasmine
Abstract: Virtual reality and other extended reality (XR) technologies are being integrated into academic libraries to support research and teaching in innovative ways; however, new technologies are often adopted without considering disabled users. XR accessibility depends on establishing appropriate policies and best practices. This paper examines the current state of XR accessibility initiatives in academic libraries by reporting findings from a survey sent to the academic library community from February to May 2021.